Unobservables in Consumer Choice: Residential Energy and the Demand for Comfort - Quigley, John M.; Rubinfeld, Daniel L. (The Review of Economics and Statistics, 1989)
A model of consumption of residential energy in dwellings is developed, distinguishing between attributes of housing that provide direct benefits to consumers and attributes that serve as inputs in the production of final goods, for example, the thermal comfort of dwellings. Empirical estimates are made of the mode, based upon the Annual Housing Survey, and the results are used to calculate the effects of changes in energy prices on the consumption of housing, residential energy, and other goods. The analysis suggests that the adjustment process within the housing market permits a great deal of substitution in response to energy price changes. Copyright 1989 by MIT Press.